The Development of an Extracurricular Activity Model Based on Religious Strengthening in Building MAN Batusangkar Students’ Characters - Yasmansyah, Yasmansyah; Ahida, Ridha; Sesmiarni, Zulfani; Hanani, Silfia (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
The decline in religious values and morals among students in Tanah Datar Regency indicates a significant moral crisis. Morals are an important foundation for obtaining blessed knowledge. The school and community need Immediate and strategic action to overcome this problem and create a generation that is not only academically intelligent but also noble and religiously observant. This research employed development research (Research and Development). The data source of this research was PAI (Islamic Religious Education) teachers at four MAN (Islamic Senior High Schools) in Tanah Datar Regency. The data collection techniques were observation, interview, questionnaire, and documentation. The data analysis techniques used were descriptive, qualitative, and quantitative. The results showed that the validity of the model of extracurricular activities based on religious strengthening in the character building of students obtained an average of 100% with a highly valid category. The results of the practicality test obtained an average of 91.7% in the very practical category. Thus, the model of extracurricular activities based on religious strengthening in character building is declared very effective